Ang kritika ay pagsusuri na/ng may sinasabi mga piling sanaysay - Nuncio, Rhoderick V.; De La Salle University Publishing House (Manila De La Salle University Publishing House, 2019)
On how to do Philippine literary criticism.
Includes bibliographical references (pages 279-289).
In Tagalog.
Keywords: Criticism -- Philippines; Discourse analysis, Literary -- Philippines; Literature -- History and criticism